The appropriation of autopoiesis in architecture - Guillermo Sánchez Sotés; Thomas Fischer; Christiane M. Herr (Frontiers of Architectural Research)
This study investigates the merits of the cross-disciplinary appropriation of the theory of autopoiesis in Patrik Schumacher's The Autopoiesis of Architecture. In this two-volume work, Schumacher builds upon Luhmann's sociological adoption of Maturana et al.’s biological theory of autopoiesis. This lineage of repeated appropriation raises questions about the merits of the cross-disciplinary appropriations of natural-scientific theory in architecture in general and the appropriation of autopoiesis in architectural theory in particular. Specifically, what are the merits of Schumacher's appropriation of the theory of autopoiesis? In this article, we develop and apply a text analysis method drawing on discourse analysis, close reading, visual interpretation, and “inference to the best explanation” to analyse a set of three pertinent samples from The Autopoiesis of Architecture. Our analysis, using previously established categorisations of language use and merits of theory appropriation, shows that Schumacher employs various modes of language use in The Autopoiesis of Architecture to reference both prior instances of autopoiesis. These ambiguities serve to achieve merits that, in many cases, seem to benefit the author rather than his readers.